2011
DOI: 10.1007/s10353-011-0618-6
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes of lung transplant in idiopathic pulmonary fibrosis

Abstract: Background: Idiopathic pulmonary fibrosis (IPF) is currently the main indication for lung transplant (LTx) in the United States. Opinions differ regarding the outcomes in IPF compared to other conditions. This study compares the short-term outcomes of LTx in IPF versus non-IPF as well as single lung transplant (SLT) versus bilateral lung transplant (BLT) in IPF patients in a large nationally representative sample.Methods: We performed a secondary analysis of the Nationwide Inpatient Sample (1988)(1989)(1990)(1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…An analysis of transplants among IPF patients from 2006 – 2010 included in the Spanish Lung Transplant Registry reported 3-month post-transplant survival of ~80% and 1-year survival of ~63% [ 27 ]. An analysis of the US Nationwide Inpatient Sample from 1988 to 2006 found that in-hospital survival among IPF patients who received lung transplants was 91% [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of transplants among IPF patients from 2006 – 2010 included in the Spanish Lung Transplant Registry reported 3-month post-transplant survival of ~80% and 1-year survival of ~63% [ 27 ]. An analysis of the US Nationwide Inpatient Sample from 1988 to 2006 found that in-hospital survival among IPF patients who received lung transplants was 91% [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two papers reported data on post-transplant in-patient mortality. From an analysis of the US National Inpatient Sample database, in-hospital death was significantly ( P = 0.006) greater following SLT (16%) vs. BLT (5%) [ 28 ]. From a small single center study from the US that included 45 IPF patients, there was no significant difference in in-hospital mortality between BLT (9.4%) and SLT (9.4%) [ 41 ].…”
Section: Resultsmentioning
confidence: 99%